Resposta :
Resposta:
OLÁ
[tex]f(x) = 2x - 5 \\ para \: x = - 5 \\ substitui \\ f(x) = 2x - 5 \\ f( - 5) = 2 \times ( - 5) - 5 \\ f( -5) = - 10 - 5 \\ \red{f( - 5) = - 15}[/tex]
Explicação passo-a-passo:
espero ter ajudado
![Ver imagem ANDREYLUCAS15399](https://pt-static.z-dn.net/files/d89/15f86e1b1216c9ee0814348d606851b1.jpg)
Resposta:
OLÁ
[tex]f(x) = 2x - 5 \\ para \: x = - 5 \\ substitui \\ f(x) = 2x - 5 \\ f( - 5) = 2 \times ( - 5) - 5 \\ f( -5) = - 10 - 5 \\ \red{f( - 5) = - 15}[/tex]
Explicação passo-a-passo:
espero ter ajudado